1993
DOI: 10.1161/01.hyp.22.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of intracellular sodium by vasopressin in spontaneously hypertensive rats.

Abstract: The arginine vasopressin-induced increase in intracellular sodium concentration was augmented in cultured rat vascular smooth muscle cells derived from 12-week-old spontaneously hypertensive rats (SHR) compared with those from 12-week-old normotensive Wistar-Kyoto (WKY) rats. This difference was enhanced by treatment with a Na + ,K + -ATPase inhibitor, ouabain. The calcium-free state did not affect the basal intracellular sodium concentration but completely blocked the arginine vasopressininduced increase in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In the present study, plasma AVP levels increased significantly in young SHR during the development of hypertension which agrees with results in the previously cited reports. In vivo and in vitro studies revealed that enhanced responsiveness to AVP via the V 1A and V 2 receptors also occurs in severel hypertension model systems [13,14,28,29]. Jeffries et al [14] reported that AVP plays an important role in sodium retention governed by V 2 receptors in deoxycorticosterone acetate/ salt induced hypertension in rats and suggested that exaggerated V 2 receptor mediated responses in the distal cortical nephron may play an important role in the pathogenesis of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, plasma AVP levels increased significantly in young SHR during the development of hypertension which agrees with results in the previously cited reports. In vivo and in vitro studies revealed that enhanced responsiveness to AVP via the V 1A and V 2 receptors also occurs in severel hypertension model systems [13,14,28,29]. Jeffries et al [14] reported that AVP plays an important role in sodium retention governed by V 2 receptors in deoxycorticosterone acetate/ salt induced hypertension in rats and suggested that exaggerated V 2 receptor mediated responses in the distal cortical nephron may play an important role in the pathogenesis of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium transience of the EBs and rat neonatal cardiomyocytes was measured as described previously 16. Briefly, cells were loaded with fura‐2‐AM (Dojin Biochemicals, Kumamoto, Japan), washed and transferred to the chamber of a fluorescence spectrophotometer (CAF‐100; Japan Spectroscopic Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Several binding studies provide support for the view that the Okamoto-Aoki strain difference in vascular reactivity is due to greater V 1 receptor number, without any change in receptor affinity. In one study, the density of AVP receptors was found to be five times greater in cultured thoracic aortic smooth muscle cells of 12-wk-old SHR, either in proliferative or quiescent states, compared with those from WKY (34). In a recent study on freshly isolated smooth muscles cells from preglomerular vessels, we observed a more pronounced increase in cytosolic calcium after AVP stimulation in 7-wk-old SHR compared with WKY (20).…”
Section: Discussionmentioning
confidence: 76%